Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1055/s-0035-1558986
|View full text |Cite
|
Sign up to set email alerts
|

Striving for Normalcy after Lower Extremity Reconstruction with Free Tissue: The Role of Secondary Esthetic Refinements

Abstract: A significant portion of patients desire secondary revisions following the initial procedure. This is especially true of younger patients with below ankle reconstruction. In many patients, an esthetic consideration should not be of secondary concern, but should be part of the ultimate reconstructive algorithm for lower extremity limb salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…14 To overcome this limitation, immediate debulking of ALT flaps elevated subfascially or suprafascially has been described prior to inset, especially among younger patients. 4 However, partial flap loss that is most likely explained by the interruption of the flap's microcirculation, may occur. 28,29 Microdissection techniques to improve flap safety are tedious and time consuming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 To overcome this limitation, immediate debulking of ALT flaps elevated subfascially or suprafascially has been described prior to inset, especially among younger patients. 4 However, partial flap loss that is most likely explained by the interruption of the flap's microcirculation, may occur. 28,29 Microdissection techniques to improve flap safety are tedious and time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Primary and secondary debulking procedures have therefore been introduced and are widely used in many centers. 4 In primary thinning, relatively large fat lobules that lie deeply to the superficial fascia are removed after elevation of the flap. However, primary thinning may lead to partial loss of the flap when conducted too aggressively with the destruction of small veins.…”
mentioning
confidence: 99%
“…They found that approximately 20% of their patients underwent secondary procedures to improve the contour and esthetics of the free flap. The procedures included complex local tissue rearrangement or debulking, direct scar excision, liposuction and laser scar treatment 15 . In our series, 4 patients (19%) out of the cohort that had successful lower extremity salvage ultimately underwent secondary debulking procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite its popularity, the ALT flap is not without limitations in the coverage of lower extremity defects. Specifically, in the treatment of small and medium sized defects of the lower extremity, the ALT flap often requires multiple secondary operations for flap debulking, as it does not atrophy over time 15 . Furthermore, for reconstruction of foot and ankle defects, the bulk of the ALT flap impairs aesthetic outcomes and hinders shoe and orthotic fitting which is a significant limitation for return to functional activity 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Nelson et al reported 21.1% of their 152 patients underwent secondary aesthetic revisions again with debulking being the most common procedure. 65 However, they did not compare fasciocutaneous versus muscle groups. In our experience, free muscle flaps with an unmeshed skin graft provide durable coverage and muscle atrophy leads to acceptable contouring if inset well at initial operation.…”
Section: Principles Of Surgical Treatmentmentioning
confidence: 99%